Sistem Pemantau dan Pengendali Suhu Ruang Server Menggunakan Fuzzy Berbasis Mikrokontroler RobotDyn - Budi Indra Gunawan; Unan Yusmaniar Oktiawati (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2020)
Server role becomes very important to provide service to clients. Therefore the performance of the server needs to be maintained. The performance of the server is not only influenced by the technology of the hardware but also influenced by server room ideal temperature and humidity condition. Monitoring and adjusting temperature condition is not possible to be done continuously manually because of limited human resources. One of the solutions is using a system based on the Internet of Things (IoT). This research proposed a prototype of server room temperature and humidity real-time monitoring system using RobotDyn ATmega+ESP8266 microcontroller and the Blynk IoT platform. The prototype also can maintain the temperature of server room on ideal condition by controlling Air Conditioner using Fuzzy logic Mamdani Method and infrared communication. The result of this research a prototype that can read temperature and humidity of server room accurately realtive error for temperature is 0,81% and relative error for humidity is 4,52%. Quality of Service for data transmission from prototype to Blynk Platform is very good, with average delay 127.54ms, average packet loss ratio 0.54%, average packet delivery ratio 99.46%, and average throughput 10.5 kbps. Control System that built using fuzzy logic Mamdani Method can automatically control the value of Air Conditioner temperature output that adjust the condition of server room with maximum range for control Air Conditioner is 4 meters and 45° from Air Conditioner’s transmitter